2017
DOI: 10.1002/cctc.201700269
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Various Chlorides on Xylose Conversion to Furfural: Experiments and Kinetic Modeling

Abstract: In this paper, the catalytic activity of thirteen different metal chlorides in aqueous solution for the conversion of xylose into furfural was studied in comparison with both the auto‐ and HCl‐catalyzed reactions. A maximum furfural yield of 60.3 mol % was reached with the addition of FeCl3 to the aqueous xylose solution. However, the catalytic efficiency of FeCl3 decreased on use of birch hydrolysate as a raw material, resulting in 43.5 mol % furfural yield. The obtained experimental results were incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 47 publications
(80 reference statements)
7
26
0
Order By: Relevance
“…The FUR yield increased from 37 mol% to 68% with an increasing time from 30 to 90 min at 190 °C when employing an aqueous to CPME phase ratio of 1:1 (Figure 11). The highest mole fraction of hydroxymethylfurfural (HMF) was 0.01 mmol ( Figure A12 in the Supporting Information), which is in agreement with previous studies when using birch hydrolysate to produce FUR from pentoses [70]. °C in 180 min was 78% in the case of CPME as an organic solvent phase.…”
Section: Furfural Production From Birch Hydrolysatesupporting
confidence: 89%
“…The FUR yield increased from 37 mol% to 68% with an increasing time from 30 to 90 min at 190 °C when employing an aqueous to CPME phase ratio of 1:1 (Figure 11). The highest mole fraction of hydroxymethylfurfural (HMF) was 0.01 mmol ( Figure A12 in the Supporting Information), which is in agreement with previous studies when using birch hydrolysate to produce FUR from pentoses [70]. °C in 180 min was 78% in the case of CPME as an organic solvent phase.…”
Section: Furfural Production From Birch Hydrolysatesupporting
confidence: 89%
“…However, the significantly highest furfural yield (68%) and selectivity (70%) were achieved using iron chloride as a catalyst. Our result agrees with the literature, as many studies have shown that FeCl 3 produces the highest furfural yield in water media compared to other metal halides [7,10]. The 68% furfural yield achieved in our study with FeCl 3 catalyst is also comparable to that found in other studies.…”
Section: Furfural Production Using Homogeneous Catalystssupporting
confidence: 92%
“…Different metal salts have been studied in the literature but it was important to perform tests in our reaction system, using microwave heating and water/MIBK media. Reactions were performed at a temperature of 160 • C, a reaction time of 1.5 h and a catalyst amount of 0.05 mmol, based on the literature [10]. Almost full xylose conversion (98%-99%) was achieved using all catalysts other than zinc chloride, which yielded only 91% conversion (Figure 2, asterisks).…”
Section: Furfural Production Using Homogeneous Catalystsmentioning
confidence: 99%
See 2 more Smart Citations